PENGARUH PROFITABILITAS, GOOD CORPORATE GOVERNANCE, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - Najihah, Alfi; Bhayangkara, I.B.K. (JEA17: Jurnal Ekonomi Akuntansi, 2017)
ABSTRACTThis study aimed to test the "Influence of profitability, good corporate governance and company size on the value of the company". Objects used in this study is the food and baverage company listed on the Indonesia Stock Exchange (BEI) in the period 2013 to 2015. The population used in this study is seluh Food and Beverage companies listed in Indonesia Stock Exchange as many as 14 companies. The sampling technique is done is purposive sampling method with the following criteria: (1) Food and Beverage Companies that go public or be listed in the Indonesia Stock Exchange (BEI) during the period from 2013 to 2015, (2) Food and Beverage Company that publishes reports annual (annual Report) during the period from 2013 to 2015, (3) There is a report on the managerial ownership, institutional ownership, the number of board members komimsaris, the number of independent board members, the number of board members, and the number of audit committee members. The number of samples that meet the criteria as much as 5 companies with a span of 3 years of research. Data were analyzed using multiple linear regression analysis. The data is first performed classic assumption test before hypothesis test. Testing the hypothesis in this study using a test using the coefficient of determination, test pasrial / t test and simultaneous / f test. The results showed that the coefficient of determination obtained adjust the value of R Square of 37.9%. Partial assay results indicate the variable (1) Profitability no significant effect on the value of the company (2) Good corporate governance significant effect on the value of the company. (3) The size of the company a significant effect on the value of the company. (4) Profitability, good corporate governance and firm size simultaneously significant effect on firm value The conclusion in this study good corporate governance and company size is a variable that affects the value of the company. Good governance and the size of the company's high will bring a positive signal to investors that the company's value will increase. Keywords: Profitability, Good Corporate Governance, Company Size, and    Company Value.